The Legal Nature of Force-Majeure - Isanov, Kholmurod Ruzievich (RA Journal Of Applied Research, 2021)
This article analyzes the legal nature of the force majeure in the system of legal relations. The will of the parties to a force majeure legal relationship, as a sudden or unavoidable event or situation involving their will, affects the rights and obligations between them and has certain legal consequences, the whole system of legal relations has also been examined as the basis for exemption from liability or exclusion of liability. Approaches have also been explored in distinguishing a situation that led to harm as a risk (risk) or force majeure situation in determining liability for breach of obligation. The conditions for the use of force majeure in the continental and general legal systems are analyzed, and scientific conclusions are drawn on its legal nature and its role in the national legal system.